2006
DOI: 10.1073/pnas.0606330103
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of silicon in the Arabidopsis –powdery mildew pathosystem

Abstract: The role and essentiality of silicon (Si) in plant biology have been debated for >150 years despite numerous reports describing its beneficial properties. To obtain unique insights regarding the effect of Si on plants, we performed a complete transcriptome analysis of both control and powdery mildew-stressed Arabidopsis plants, with or without Si application, using a 44K microarray. Surprisingly, the expression of all but two genes was unaffected by Si in control plants, a result contradicting reports of a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
206
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(221 citation statements)
references
References 53 publications
11
206
1
3
Order By: Relevance
“…We have been able to show a clear if qualitative relationship between the induction of callose and deposition of biogenic silica in Arabidopsis, a plant not known for accumulating significant amounts of silica in its leaves. Our results for callose induction strongly support research identifying a role for callose in resistance to powdery mildew in Arabidopsis [4] while our findings for silica deposition suggest a mechanism for silicon-induced resistance to the same pathogen in Arabidopsis [7,8]. We reported previously that callose-associated silica deposition provided protection against powdery mildew in Equisetum arvense (horsetail) and 8 we speculated that biogenic silica presented a physical barrier to the entry of the pathogen [3].…”
Section: Identification Of Callose In Leavessupporting
confidence: 88%
“…We have been able to show a clear if qualitative relationship between the induction of callose and deposition of biogenic silica in Arabidopsis, a plant not known for accumulating significant amounts of silica in its leaves. Our results for callose induction strongly support research identifying a role for callose in resistance to powdery mildew in Arabidopsis [4] while our findings for silica deposition suggest a mechanism for silicon-induced resistance to the same pathogen in Arabidopsis [7,8]. We reported previously that callose-associated silica deposition provided protection against powdery mildew in Equisetum arvense (horsetail) and 8 we speculated that biogenic silica presented a physical barrier to the entry of the pathogen [3].…”
Section: Identification Of Callose In Leavessupporting
confidence: 88%
“…TFs often exhibit low-level and highly localized expression changes; therefore, we expected our site-specific expression analysis to identify unique TFs with important functional roles in the PM interaction. We found 67 TFs exhibited altered expression at the site of infection, with 79% not previously associated with a compatible PM interaction (4,(7)(8)(9). Although many of these PM site-specific TFs have no defined function, we identified sets of TFs associated with the following processes: photosynthesis, drought/cold tolerance, pathogen defense and cell death, auxin signaling/response, and the cell cycle (Fig.…”
Section: Site-specific Profiling Identifies Previously Hidden Localizmentioning
confidence: 94%
“…3A and SI Appendix). Although a decrease in photosynthesis-associated gene expression had previously been observed in whole leaves in response to PM (4,7,11), our focus at the site of infection allowed us to identify a more extensive set of altered photosynthesis-related genes. It also eliminated potential complications associated with differential PM-induced impacts on photosynthesis at the site of infection compared with nearby or distal sites.…”
Section: Pm Site-specific Profiling Supports Diminished Photosynthesimentioning
confidence: 99%
“…A study by Kauss et al (2003) conducted on cucumber leaves and investigating the process of plant infection showed that resistance to infection can be acquired by the expression of a protein rich in proline together with the presence of silica at the site of pathogen penetration. Fauteux et al (2006) stated that only two genes were upregulated when silicon alone was applied to Arabidopsis plants. Brunings et al (2009) studied the gene expression of silicon-treated rice using a microarray and found diff erential regulation of 221 genes compared to untreated control, including some transcription factors.…”
Section: Molecular Mechanismmentioning
confidence: 99%
“…By using Agilent 44K oligo DNA arrays, it has been shown that silicon increased signifi cantly the level of photorespiration in rice leaves infected by Cochliobolus miyabeanus (Van Bockhaven et al, 2014). Genome-wide studies on tomato, rice, Arabidopsis and wheat grown in soil amended with silicon and compared to non-amended control plants have shown a diff erential and unique expression of a large number of genes involved in host plant defense mechanisms or metabolism (Watanabe et al, 2004;Fauteux et al, 2006;Chain et al, 2009;Brunings et al, 2009;Ghareeb et al, 2011).…”
Section: Molecular Mechanismmentioning
confidence: 99%